A Strategy towards Team Integration Practice for Improving the Design and Construction Process in the Malaysian Industrialized Building System Projects - Othman, Mohd Zainudin; Nawi, Mohd Nasrun Mohd; Nifa, Faizatul Akmar Abdul; Yaakob, Mazri; Rofie, Khadafi; Zan, Zainal Md; Pozin, Mohd Affendi Ahmad (International Review of Management and Marketing, 2016)
The Malaysian construction industry has been urged to change from using a conventional method to industrialized building system (IBS) to attain, (1) better build quality and productivity, (2) reduce risks related to occupational safety and health, (3) alleviate issues for skilled workers and dependency on manual foreign labor, and (4) achieve the ultimate goal of reducing the overall cost of construction. Despite acknowledging its benefits, the construction industry is still not rapidly embracing IBS. This is mainly due to its traditional and conservative nature where anything new or different, faces implementation barriers. An investigation by some researchers identified that one of the main obstacles to IBS implementation in the Malaysian construction industry is related to poor integration among stakeholders involved during the design stage. Responding to the issue above, this research aims to counter this problem and help towards the betterment of the IBS Malaysian construction industry using an integrated design team delivery approach. Therefore, this paper discusses a strategy by the identifying key factors that are pertinent to improving the integration of design and construction activities and summarizes the recommendations from multiple case studies on the key factors towards effective integrated design team delivery. Keywords: Industrialized Building System, Integration, Integrated Practiced, Key Factor JEL Classifications: L14, L74, L88